A giant water bug from the Lower Cretaceous Crato Formation of Brazil (Heteroptera: Belostomatidae: Lethocerinae) - Nel, André; Waller, Alain (Zootaxa, 2006)
The oldest indisputable representative of the subfamily Lethocerinae, Lethocerus vetus sp. n., is described from the Early Cretaceous crato Formation in Brazil. Its preserved structures are nearly identical to those of Recent Lethocerus.